2013
DOI: 10.15376/biores.9.1.938-951
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Modelling of Silica Bodies from Oil Palm Empty Fruit Bunch (OPEFB) Fibres

Abstract: Investigating the mechanical behaviour of silica bodies in oil palm empty fruit bunches (OPEFB) is important to improve the process of silica body removal. This study will assist in providing an understanding of the role of OPEFB as a bioresource material for the bioconversion process. The microstructure of silica bodies/protrusions on the OPEFB fibre surface was modelled using the finite element method, based on the information obtained from scanning electron microscopy (SEM). The effects of silica body geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 26 publications
3
26
1
Order By: Relevance
“…The oxidation process assisted with Fenton reagents showed some improvement of the delignification process along with the removal of silica bodies. Therefore, the removal of silica bodies could expose siliceous pathways and allow more exposure towards an amorphous region, which results in better hydrolysis performance (Omar et al 2014). In determining functional groups changes, the FTIR spectra of the raw EFB fibers was consistent with the content of lignocellulosic materials, including the presence of carbonyl and carboxyl, with the stretching of 1700 cm -1 and hydroxyl groups with a broad band of 3600 cm -1 to 3000 cm -1 (Fig.…”
Section: Characterization Pretreated Efb Fibersmentioning
confidence: 78%
“…The oxidation process assisted with Fenton reagents showed some improvement of the delignification process along with the removal of silica bodies. Therefore, the removal of silica bodies could expose siliceous pathways and allow more exposure towards an amorphous region, which results in better hydrolysis performance (Omar et al 2014). In determining functional groups changes, the FTIR spectra of the raw EFB fibers was consistent with the content of lignocellulosic materials, including the presence of carbonyl and carboxyl, with the stretching of 1700 cm -1 and hydroxyl groups with a broad band of 3600 cm -1 to 3000 cm -1 (Fig.…”
Section: Characterization Pretreated Efb Fibersmentioning
confidence: 78%
“…In the first region where strain was less than about 0.03, damage within the microstructure of the fibre was thought to be minimal and the stress-strain curve showed linear elastic behaviour. For strains beyond 0.03, the plastic region was observed where Omar et al (2014), through a numerical work, suggested that the region is related to the debonding of the silica-body and OPEFB fibre interface. Finally, in the fracture region, fracture or total failure of OPMF was observed from the sudden drop of stress.…”
Section: Microstructure Of Opefbmentioning
confidence: 94%
“…The shredded samples were then kept in a conditioned environment at -20 C prior to tensile tests and SEM analysis. Omar et al (2014). "Modelling of SiO2 bodies," BioResources 9(4), 7041-7058. 7043…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations